BRAVE NEW DIGITAL WORLD? REFLECTIONS ON THE WORLD SUMMIT ON THE INFORMATION SOCIETY - Leuprecht, Peter (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2005)
The World Summit on the Information Society (WSIS) is organized in two parts: the first part in Geneva in December 2003, the second part in Tunis in November 2005. The WSIS is an initiative of the International Telecommunications Union (ITU), a technical organization in which corporate interests carry considerable weight. This inevitably has an influence on the orientation of the Summit. The texts adopted by the first phase of the WSIS project a naïve belief in technology and in a brave new digital world in which Information and Communication Technologies (ICTs) will solve all problems. In reality, they cover up fundamental disagreements and diametrically opposed world views. The digital divide is no more than a symptom of the unequal distribution of wealth among and within countries. Any serious policy of ICT development must be part and parcel of a global policy of human and sustainable development. The main contentious issues of the first part of the WSIS were human rights, Internet governance, free software, intellectual property rights and the financial means of bridging the digital divide. This first phase of the WSIS gives rise to a number of critical reflections on the present state of the international community. The first part of the World Summit on the Information Society (WSIS) took place in Geneva, Switzerland, from 10 to 12 December 2003. Its second part is to be held in Tunis, Tunisia, from 16 to 18 November 2005. The purposes of this article are (I) to give a brief account of the preparation and organization of the Summit, (II) to present the main results of its first phase, (III) to deliver a critical analysis of these results, and (IV) to show that the WSIS gives rise to some critical reflections on the present state of the international community.